Central Bank Financial Policy Mechanism and Taxation Earning in Sub-Saharan Africa - Omodero, Cordelia Onyinyechi (Ekonomika, 2025)
A strong monetary policy is critical to the overall health of an economy. Again, funding availability for firms is crucial and acts as a spur for well-designed monetary policy. The implications are far-reaching and have an impact on government revenue collection, which helps to enhance social welfare since providing basic social amenities is an essential component of effective governance, particularly in Sub-Saharan Africa (SSA). Thus, the purpose of this study is to investigate the impact of monetary policy on tax revenue growth in SSA. The investigation makes use of data from the World Bank Development Indicators and the International Monetary Fund spanning the years 1990–2022. The study also uses the autoregressive distributed lag (ARDL) approach to investigate the short- and long-run relationships between monetary policy instruments and tax revenue growth. Monetary policy methods employed include monetary authority credit to the private sector, domestic credit to the private sector, and wide money supply, while the tax revenue growth proportion to GDP is used. According to the findings, both the monetary authority and domestic credit to the private sector have considerable negative influences on tax revenue growth, whereas wide money has an encouraging but small effect. The consequence is that the private sector in SSA is underfinanced, making it harder for the government to collect substantial tax income to meet social duties. The paper recommends that the government and monetary authorities in SSA should adopt stronger monetary policies that promote private sector business growth, which, if implemented, will result in tax revenue increase.